平面齿轮的高阶接触啮合理论 - 邹昌平; 刘鹄然 (Jixie chuandong)
In view of the high power transmission gears in practical application, a new kind profile with the best load capacity both in contact and bending strength is presented. This is a kind of gearing with equal meshing curvature over the whole tooth surface. The forming principle of this tooth is analyzed.